2020
DOI: 10.30743/best.v3i2.3224
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Penerapan Manajemen Dengan Kinerja Petugas Kesehatan

Abstract: Kinerja merupakan salah satu faktor yang sangat penting dalam sebuah organisasi. Pihak manajemen juga dapat menggunakan pengukuran kinerja sebagai alat untuk mengevaluasi organisasi. Dalam rangka peningkatan manajemen di tingkat Puskesmas, maka unsur-unsur manajemen yang terdiri atas perencanaan, penggerakan pelaksanaan dan pengawasan, pengendalian dan penilaian telah dikernbangkan. Penerapan fungsi-fungsi manajemen sangat berpengaruh terhadap kinerja pegawai puskesmas. Penelitian bertujuan untuk mengetahui hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…In the process aspect, it is known that there is no follow-up plan related to specific recommendations. Planning plays an important role in the success of an activity (Sitorus, 2020). Planning for follow-up on recommendations can include what must be done, who is doing it, what is needed and the target time for implementation (Sumadi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the process aspect, it is known that there is no follow-up plan related to specific recommendations. Planning plays an important role in the success of an activity (Sitorus, 2020). Planning for follow-up on recommendations can include what must be done, who is doing it, what is needed and the target time for implementation (Sumadi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the planning management function was also shown to be related to the success of health services. [8][9][10] Poskestren uses the principle of from, by, for and with the community, with guidance support from the government and other related elements. For this reason, a clear organization is made, such as the existence of administrators, cadres, supervisors with their respective division of duties and responsibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Sukotjo (2007) pengawasan adalah membandingkan segala sesuatu yang telah dijalankan dengan rencananya, dan dilakukan perbaikan-perbaikan bilamana terjadi penyimpangan. Pengawasan dan pengendalian adalah proses untuk Lukman Effendhi Ary Sutrischastini mengamati secara terus menerus pelaksanaan kegiatan sesuai rencana yang sudah disusun dan mengadakan perbaikan jika terjadi penyimpanagan (Sitorus, 2020)…”
Section: Pengawasanunclassified